The cost of free money : how unfettered capital threatens our economic future - Subacchi, Paola, 1962- (Yale University Press, 2020)
A penetrating account of how unchecked capital mobility is damaging international cooperation, polarizing the economic landscape, and ultimately reshaping the global order.